2007
DOI: 10.1152/ajprenal.00014.2006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of novel zinc transporter rZip10 (Slc39a10) involved in zinc uptake across rat renal brush-border membrane

Abstract: Kaler P, Prasad R. Molecular cloning and functional characterization of novel zinc transporter rZip10 (Slc39a10) involved in zinc uptake across rat renal brush-border membrane. Am J Physiol Renal Physiol 292: F217-F229, 2007. First published June 27, 2006 doi:10.1152/ajprenal.00014.2006.-Previously, in our laboratory a 40-kDa zinc transporter protein was purified and functionally reconstituted in proteoliposomes (Kumar R, Prasad R. Biochim Biophys Acta 1419: [23][24][25][26][27][28][29][30][31][32] 1999). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…The Zip-7 gene and its expression has not been examined in normal and malignant prostate cells or tissues. Messenger RNA expression was also found for the Zip-10 family member which has been shown to be involved in zinc uptake across the brush border membrane of the kidney (Kaler and Prasad 2007). It has also been shown to be regulated by thyroid hormone in intestine and kidney (Pawan et al 2007).…”
Section: Discussionmentioning
confidence: 90%
“…The Zip-7 gene and its expression has not been examined in normal and malignant prostate cells or tissues. Messenger RNA expression was also found for the Zip-10 family member which has been shown to be involved in zinc uptake across the brush border membrane of the kidney (Kaler and Prasad 2007). It has also been shown to be regulated by thyroid hormone in intestine and kidney (Pawan et al 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Zip10 is found abundantly expressed in tissues such as small intestine, pancreas, testes, brain, liver and kidney. In mice, Zip10 has the highest expression in the liver and brain [10,15]. Additionally, in the C57BL/ 6J mouse, Zip14a expression is highest in liver, duodenum, kidney and testes, whereas Zip14b expression is highest in liver, duodenum, brain and testes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the ZIP family have been demonstrated to be involved in zinc uptake and in the release of stored zinc into the cytoplasm of cells when zinc is deficient. In mammals, Zip1-8, Zip10 and Zip14 proteins have been reported to function as zinc uptake proteins [5,[8][9][10]. For instance, in transfected cells, mZip5 functions in zinc uptake and is specific for zinc as a substrate [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the transgenic mice with three more copies of the ZIP8 gene were found to accumulate twice as much Cd in the kidney after Cd exposure, and the PT from these mice had elevated ZIP8 expression levels at the apical membrane, accounting for their high sensitivity to Cd toxicity (Nebert et al 2012). ZIP10 has been found in high abundance in renal cortical epithelial cells, suggesting the potential role for this zinc transporter in Cd reabsorption (Kaler and Prasad 2007). There is little evidence for an exit route for Cd once it has entered PT cells.…”
Section: Cadmium -From Dinner Plate To Kidney Cell Toxicitymentioning
confidence: 99%